2012
DOI: 10.1371/journal.pone.0032014
|View full text |Cite
|
Sign up to set email alerts
|

Large Aggregates Are the Major Soluble Aβ Species in AD Brain Fractionated with Density Gradient Ultracentrifugation

Abstract: Soluble amyloid-β (Aβ) aggregates of various sizes, ranging from dimers to large protofibrils, have been associated with neurotoxicity and synaptic dysfunction in Alzheimer's Disease (AD). To investigate the properties of biologically relevant Aβ species, brain extracts from amyloid β protein precursor (AβPP) transgenic mice and AD patients as well as synthetic Aβ preparations were separated by size under native conditions with density gradient ultracentrifugation. The fractionated samples were then analyzed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 53 publications
2
73
0
Order By: Relevance
“…Using density gradient centrifugation to separate protein aggregates from cell organelles such as mitochondria (Sehlin et al , 2012), we observed that a fraction of the Aβ42 peptide added to the experiment directly associated with mitochondria. Of interest, the presence of precursor proteins changed the behavior of Aβ42, as the amount of mitochondria-associated material decreased, whereas the aggregated forms increased.…”
Section: Discussionmentioning
confidence: 99%
“…Using density gradient centrifugation to separate protein aggregates from cell organelles such as mitochondria (Sehlin et al , 2012), we observed that a fraction of the Aβ42 peptide added to the experiment directly associated with mitochondria. Of interest, the presence of precursor proteins changed the behavior of Aβ42, as the amount of mitochondria-associated material decreased, whereas the aggregated forms increased.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation was incubated for 30 minutes at 37°C and then centrifuged at 16 000 × g for 5 minutes to pellet potential large aggregates. The supernatants were further purified from monomers by size exclusion chromatography (Superdex 75 column, GE Healthcare, Sweden) in 0.05 M Phosphate buffer, 0.15 M NaCl, pH 7.4, and protofibrils were collected in the void fraction as previously described . The generated Aβ protofibrils were used for the standard curves in the oligomer/protofibril assays.…”
Section: Methodsmentioning
confidence: 99%
“…The ELISA was performed as previously described [34]. In addition to Aβ40, soluble Aβ protofibril levels in brain TBS homogenates was measured as previously described [34,39]. Aβ concentrations were determined from a standard curve of serially diluted synthetic Aβ40 and Aβ protofibrils respectively.…”
Section: Biochemical Analysis Of Gfap and Aβ Pathologymentioning
confidence: 99%